KARAKTERISTIK LIMBAH CAIR PABRIK KELAPA SAWIT PADA PROSES PENGOLAHAN ANAEROB DAN AEROB - Ida Nursanti (Universitas Batanghari Jambi, 2013)
Palm oil mill wastewater ( LCPKS ) or palm oil mill effluent ( POME ) is one type of organic agro-industrial wastes . So that the waste can be useful as a fertilizer it must be free of pollutants and high nutrient levels . The research aims to determine the diversity and level of reduction of nutrient content and LCPKS contaminants in the processing of primary anaerobic pond I, II secondary anaerobic pond to the aerobic pond . The experiment was conducted at PT . Sumbertama Nusa Pertiwi District Kumpeh Hulu Muaro Jambi and in the Laboratory , lasted for 3 months . Implementation research using survey methods at the site of primary anaerobic pond treatment LCPKS I, II secondary anaerobic pond and aerobic pond LCPKS then analyzed in the laboratory . The results showed that the levels of nutrients N , P , K , COD , BOD , TSS and C - organic LCPKS acidification pond is higher than the first secondary anaerobic pond and aerobic pond , while Al and Fe content varies . Ca and Mg levels are higher in the aerobic pond . LCPKS acidification has an acidic pH , the first secondary anaerobic pond rather sour and slightly alkaline aerobic pond . Highest total in an aerobic fungi and total bacteria in an anaerobic highest first secondary .Keywords: Characteristics of Palm Oil Mill Effluent